The Impact of Bullying on the Social Development of Adolescents at SMA Negeri 1 Sungai Ambawang, Kubu Raya Regency - Shadrina, Dina Nur (Pencerah, 2024)
The aim of this research is to determine the role of schools in minimizing the impact of bullying on the social development of students at SMA Negeri 1 Sungai Ambawang. The location of this research is SMA Negeri 1 Sungai Ambawang, Kubu Raya Regency. The research subjects were members of the Violence Prevention and Handling Team (TPPK) of SMA Negeri 1 Sungai Ambawang. This research uses qualitative research. Data collection techniques in this research were observation, interviews and documentation. The data analysis techniques used are data collection, data reduction, data presentation, verification. The results of this research are the role of SMA Negeri 1 Sungai Ambawang school in creating Anti-bullying Programs and Policies; the school formed a special team, namely the Violence Prevention and Handling Team (TPPK); The monitoring system implemented is in collaboration with all school officials to monitor and pay attention to bullying in the classroom. There is a school community approach at SMA Negeri 1 Sungai Ambawang, namely teachers and the PPK Team play a role in providing guidance, direction, support and protection to students; provide an understanding of the dangers of bullying towards students by providing outreach; ascertain where bullying occurs by seeking information about acts of bullying that students often experience at school; handling of bullying cases is carried out through discussions with parents, teachers and third parties, namely the police as mediation intermediaries, providing guidance and supervision to students; The school will collaborate with the Kubu Raya Regency Women's Empowerment and Child Protection Service.